PERKEMBANGAN, CABARAN DAN SUMBANGAN ARKEOLOGI AWAM DI MALAYSIA: (Development, Challenges, And Contributions Of Public Archaeology In Malaysia) (Applied History Journal of Merong Mahawangsa, 2024)
Arkeologi awam di Malaysia telah berkembang dengan ketara melalui integrasi pelbagai amalan. Arkeologi awam merujuk kepada usaha untuk melibatkan masyarakat dalam pemuliharaan, meningkatkan pemahaman warisan arkeologi dan membangunkannya menjadi sumber ekonomi baru. Artikel ini memberikan gambaran menyeluruh mengenai arkeologi awam di Malaysia dengan menyoroti sejarah, amalan semasa dan isu-isu utama yang dihadapi dalam pemeliharaan dan promosi warisan arkeologi. Amalan semasa arkeologi awam di Malaysia merangkumi usaha untuk penglibatan komuniti, pendidikan komuniti, penglibatan dalam pengurusan, promosi dan arkeopelancongan. Antara isu dan cabaran utama adalah tekanan pembangunan ekonomi yang pesat, kekurangan pakar mahir, penglibatan komuniti serta rangka kerja perundangan dan penguatkuasaan yang kukuh. Kesimpulannya, bidang arkeologi awam memerlukan kerjasama daripada kerajaan, agensi swasta dan pihak berkepentingan untuk menjayakan usaha ini.ABSTRACTPublic archaeology in Malaysia has significantly evolved through the integration of various practices that engage the community in the understanding, preservation of archaeological heritage, and economic development through archaeotourism. This article provides a comprehensive overview of public archaeology in Malaysia, highlighting its history, current practices, as well as the issues and challenges in the preservation and promotion of archaeological heritage. The study employs a qualitative approach by collecting secondary data related to public archaeology in Malaysia. The development of public archaeology has been achieved through various initiatives such as community education, archaeotourism promotion, and community involvement in the management of archaeological sites. These efforts not only help protect historical sites but also foster community appreciation for cultural heritage. However, the field continues to face challenges such as development pressure, a shortage of experts, and limited community involvement. This study also discusses the contributions of public archaeology in education, research, and the economy, while emphasizing the need for improvements in the legal framework, broader community engagement, and collaboration among stakeholders to ensure the sustainability of Malaysia’s archaeological heritage.